Label-free quantitative lymphocyte activation profiling using microfluidic impedance cytometry - Petchakup, Chayakorn (2022)
Circulating lymphocytes are integral components of our adaptive immunity with emerging clinical applications in immune status monitoring in infectious diseases and cell-mediated cancer immunotherapies. Herein we present a novel impedance-based microfluidic assay for label-free lymphocyte activation profiling based on native or antigen-specific T-lymphocyte biophysical responses. Single cell impedance profiling of T-lymphocytes first revealed distinct biophysical differences in cell size and membrane electrical impedance of healthy, activated (CD3/CD28) and dead lymphocyte populations. Impedance characterization of peripheral blood mononuclear cells (PBMCs) stimulated with mitogen phytohemagglutinin (PHA) or Tuberculin Purified Protein Derivative antigen (PPD) after 24 h also showed an increase in lymphocyte cell size (∼8 to 10 μm) which corresponded to activated lymphocytes (CD69+CD137+). We next developed a spiral inertial microfluidics cell sorter integrated with coplanar electrodes for direct impedance quantification of activated lymphocytes. By removing non-activated smaller lymphocytes (< 8 μm) and employing hydrodynamic-based single stream particle focusing, we demonstrated significant enrichment of activated lymphocytes (∼11.7-fold) to electrically detect low levels of lymphocyte activation (< 5%). Finally, the developed biochip is coupled with magnetic activated cell sorting (MACS) to quantify CD4+ T-lymphocytes response in PBMCs stimulated with PPD. A differential impedance cell count ratio (stimulated/unstimulated) was defined to distinguish activated T-lymphocytes, which showed better sensitivity as compared to immunophenotyping by flow cytometry. Taken together, the integrated impedance biosensor can be further developed as a rapid multiplexed screening assay to detect antigen-specific T-lymphocyte responses to characterize host immunity and diagnosis of infectious diseases (e.g tuberculosis, dengue and COVID-19).